The intersection between trade liberalisation and carbon emissions : an appraisal of the agreement establishing the African continental free trade area - Masamba, Magalie (University of Pretoria, 2023)
Mini Dissertation (LLM (Trade and Investment Law in Africa))--University of Pretoria, 2023.